A short-term approach for promoting oral health of internally displaced children with PTSD: the key is improving mental health-results from a quasi-randomized trial - Sulaf Hamid; Mayssoon Dashash; Youssef Latifeh (BMC, 2021)
Abstract Background Several studies have demonstrated that mental (MH) and oral health (OH) of displaced children are negatively affected during the wartime. This may be a result of general self-neglect and psychological suffering. Therefore, previous studies suggested that psychosocial support (PSS) is essential during and after humanitarian crises to prevent immediate and long-term MH and OH problems. This study was undertaken to evaluate the effectiveness of a short-term approach in improving (MH) and (OH) of displaced children suffering from posttraumatic stress disorder (PTSD). Methods A quasi-randomized clinical trial study was carried out including (118) displaced children suffering from PTSD. The Child Post-Traumatic Stress Reaction Index (CPTSD-RI) was utilized for the diagnosis of PTSD. Children were assigned into two groups (intervention and control group). Children in the intervention group were enrolled in a 6-week PSS program that contained oral health educational components designed especially for this study. Clinical evaluation included plaque index (PI) and gingival index (GI). Oral health related Quality of life (OHRQoL) was also evaluated using child perception questionnaire (CPQ11-14). Study variables were evaluated at baseline and at the end of the program for both groups. Wilcoxon rank test and t-test for independent samples were used for data analysis. Results A total of 118 children, aged between 9 and 14 years, participated in the recent study (mean age 11.0 ± 1.4). All participated children were previously diagnosed with PTSD. At baseline, there were no significant differences in the study variables between groups (P > 0.05). At the end of the program, children in the intervention group had significantly decreased PI, GI, CPQ11-14 and CPTSD-RI compared to their baseline scores (P = 0.000). In contrast, controls showed no differences at the end of the program (P > 0.05). Children in the intervention group had significantly (P = 0.000) lower PI (1.52 ± 0.55) and GI (1.48 ± 0.56) when compared to controls (PI = 1.89 ± 0.39, GI = 2.14 ± 0.32) post program. Moreover, the intervention group showed remarkable decline (P < 0.001) in their CPQ11-14 (47.16 ± 12.24) and CPTSD-RI (34.41 ± 12.23) scores compared to controls (CPQ11-14 = 72.65 ± 14.47, CPTSD-RI = 47.91 ± 14.24) post program. Conclusions The designed approach could have positive improvements in PTSD symptoms, (OH) and (OHRQoL) of displaced children. Integration between (MH) and (OH) services should be considered during and after humanitarian crises to prevent immediate and long-term MH and OH problems. Trial registration Australian New Zealand Clinical Trials Registry (ACTRN12619000285156), Date registered: 25/02/2019, retrospectively registered. https://anzctr.org.au/Trial/Registration/TrialReview.aspx?id=377001&isReview=true .